Effect of Cash Conversion Cycle, Firm Size, and Firm Age to Profitability - Ferry Christian Samosir (Pusat P2M Politeknik Negeri Batam, 2018)
This study aims to provide empirical evidence about effect of cash conversion cycle, firm size, and firm age to profitability. This study uses a quantitative approach, data collection techniques using purposive sampling method. The population in this research is manufacturing companies listed in Indonesia Stock Exchange (BEI) in the period 2012-2014 with a total sample of 101 companies and a total of as many as 303 samples of whole observation observation. This study uses panel data regression. This study was conducted to analyze the effect of the cash conversion cycle, firm size and age of the company to profitability by manufacturing companies using panel data through eviews 7.0. Establishment of a model in this study there are three models, namely common effect, fixed effect model and random effect model. Selection of the best model there are three, namely chow test, Hausman test, and langrangge multiplier. The results showed that the variable cash conversion cycle, firm size, firm age and positive effect on the variable return on assets. Variable leverage as control variables have no effect on the variable return on assets.